Transhumance in the Andes of the Altiplano: A case study in the Aimara community of Sisipa, Peru - Quispe-Martínez, Dante Euclides (2023)
The objective of the research is to describe the transhumance that is understood as the seasonal displacement of cattle in a Aymara community in the XXI century. The methodology used follows the qualitative ethnographic approach, using participant observation to accompany a family composed of eight members, with ages ranging from 8 to 80 years, who still practice the tradition of temporarily moving their livestock from the low puna to the high puna. The results obtained reveal that the shepherds move seasonally due to the exhaustion and shortage of grass in their main enclosure, a situation that leads to herd the cattle for a full day, withstanding the intense heat and the dry cold of the Altiplano. In addition, this tour is impregnated with beliefs, customs and meanings that revolve around the elements of nature and wildlife. This implies a dialog with nature, deities and divinities, followed by actions of harmony, balance and symbiosis with the environment and social life. In conclusion, it is determined that the seasonal transhumance of livestock has an experiential, community and intergenerational cycle.